2009
DOI: 10.1523/jneurosci.0887-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

HumanAPOEIsoform-Dependent Effects on Brain β-Amyloid Levels in PDAPP Transgenic Mice

Abstract: To investigate the role of human apolipoprotein E (apoE) on A␤ deposition in vivo, we crossed PDAPP mice lacking mouse Apoe to targeted replacement mice expressing human apoE (PDAPP/TRE2, PDAPP/TRE3, or PDAPP/TRE4). We then measured the levels of apoE protein and A␤ peptides in plasma, CSF, and brain homogenates in these mice at different ages. We also quantified the amount of brain A␤ and amyloid burden in 18-month-old mice. In young PDAPP/TRE4 mice that were analyzed at an age before brain A␤ deposition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
212
2
45

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(289 citation statements)
references
References 52 publications
30
212
2
45
Order By: Relevance
“…In this study, soluble apoE4/A␤ complex levels were lower than apoE2/A␤ and apoE3/A␤ complex levels in EFAD mice. These data indicate an inverse association between apoE/A␤ and oA␤ levels and are consistent with previous publications that suggest that apoE/A␤ levels isoform-specifically modulate soluble A␤ (11,15). Synapse degeneration is considered a proximal cause of cognitive deficits in AD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, soluble apoE4/A␤ complex levels were lower than apoE2/A␤ and apoE3/A␤ complex levels in EFAD mice. These data indicate an inverse association between apoE/A␤ and oA␤ levels and are consistent with previous publications that suggest that apoE/A␤ levels isoform-specifically modulate soluble A␤ (11,15). Synapse degeneration is considered a proximal cause of cognitive deficits in AD.…”
Section: Discussionsupporting
confidence: 92%
“…IHC analysis demonstrates that plaque deposition is greater with APOE4 compared with APOE3 in AD and nondemented controls (8,9) and that a higher proportion of A␤ within a plaque is associated with apoE4 than with apoE3 (10). Biochemical analysis confirms that the levels of apoE and A␤ are also higher with APOE4 compared with APOE3 in the insoluble extraction fraction from brains of FAD-Tg mice (11). Thus, APOE4 not only facilitates amyloid deposition but also forms a greater amount and/or more stable form of apoE4/amyloid than apoE3/amyloid.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Recently, Bateman and co-workers demonstrated that A␤ clearance is impaired in human late onset AD patients (5). Importantly, the APOE4 allele is associated with decreased A␤ clearance (6,7). We have demonstrated that apoE plays a direct role in the normal, physiological clearance of A␤ from the brain.…”
mentioning
confidence: 59%
“…Thus, EFAD mice are APOE-TR ϩ/ϩ /5ϫFAD ϩ/Ϫ . It should be noted, however, that the introduction of the h-APOE into FAD-Tg mouse models delays A␤ accumulation (34,50,51). Although the 5ϫFAD mice produce very high levels of primarily A␤42 and exhibit significant amyloid plaque deposition by 6 -8 weeks, introduction of APOE4 (E4FAD) delays A␤ accumulation ϳ4 months, and APOE3 (E3FAD) and APOE2 (E2FAD) delay deposition ϳ6 months (31,52).…”
mentioning
confidence: 99%